Entre fios e teias de formação : narrativas de professoras que trabalham com matemática nos anos iniciais – constituição da docência e os desafios da profissão na educação pública estadual paulista frente aos programas de governo no período de 2012 a 2015 - Montezuma, Luci Fátima (2016)
This text comes from a doctoral research, with a qualitative approach, which included the participation of nine polyvalent and experienced teachers who teach math to the early years, work in São Paulo State Public Education and, over the years of 2012 to 2015, produced autobiographical narratives, written and/or oral, from narrative interviews, considering the experienced formative processes throughout their life stories, with focused eyes mainly for mathematics, facing the implementation of government programs with focus in this discipline in the early years: Mathematics Education for the early years-EMAI and National Pact for Literacy in the Correct Age-PNAIC-Mathematics. Considering that the way of "being" a teacher is related to the established culture and to what they experienced, the aim of this study was to understand how is the teaching constitution process of experienced teachers who teach Mathematics to the early years, facing the government programs that impacted the teaching of Mathematics in the early years in the São Paulo State Public Education in the period between the years of 2012-2015, entitled of EMAI and PNAIC Mathematics, trying to understand the teaching professionally constitution process of collaborators teachers over time and to raise evidences of professional development. In this context, this work tried to answer the investigative question how gives the process of teaching formation of experienced teachers, facing both programs, and find out what impacts were generated in the teaching practice of them, since such programs, substantially interfere in the daily life schools. The theoretical basis that supported the analysis are the narrative and autobiographical researches, mainly in Bolivar, Domingo and Fernandez; Connnelly and Clandinin; Josso; Passeggi, Souza and Vicentini; and the formation training of teachers in: Mizukami et al.; Tardif and Shulman. The analysis of the narratives reveals professional development evidences of teachers from established programs, but indicates that, in the practice of the classroom, with the students, in certain situations, in front of their views already entrenched historically, teachers came into conflict with the theoretical and methodological guidelines proposed, and they take practices that could be considered creative insubordination, when the teacher dares to create and dares in teaching with the desire to promote learning in which students attribute meanings to the knowledge. The analysis reveals that, as pointed out in the field training of teachers researches, the act of teaching is to make choices in full interaction with students, starting with the knowledge of teachers, their conceptions, the ethic and the professional commitment that they have with the exercise of being a teacher. It was also observed that teachers felt discomfort in front of professional precariousness, leaving them with fear about how will be the future of this category and sometimes even a teacher unease.